2022
DOI: 10.1111/ced.15038
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of LAT1 in basal cell carcinoma: implications for tumour cell survival

Abstract: Summary Background Basal cell carcinoma (BCC) is the most common type of cancer in fair‐skinned individuals worldwide. Altered metabolism is a hallmark of cancer, and a growing body of evidence has shown increased expression of the large neutral amino acid transporter small subunit 1 (LAT1) in several types of cancers, including BCC. However, the mechanisms behind changed LAT1 expression in BCC are largely unknown. Aim To describe the protein expression of LAT1 and its colocalization with LAT2, and to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Apart from the well-known Warburg effect, metabolic alterations in lipid and amino acid metabolism have been observed in a number of tumors, including colorectal cancer, lung cancer, and breast cancer ( 7 ). Mounting evidence have indicated that changes in amino acid metabolism contributed to the metastasis, proliferation, angiogenesis, and drug resistance of colorectal cancer ( 8 11 ). Recent study has demonstrated that inhibition of ASCT2 (function as a glutamine transporter) exerted a great anti-tumor effect in colorectal cancer ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the well-known Warburg effect, metabolic alterations in lipid and amino acid metabolism have been observed in a number of tumors, including colorectal cancer, lung cancer, and breast cancer ( 7 ). Mounting evidence have indicated that changes in amino acid metabolism contributed to the metastasis, proliferation, angiogenesis, and drug resistance of colorectal cancer ( 8 11 ). Recent study has demonstrated that inhibition of ASCT2 (function as a glutamine transporter) exerted a great anti-tumor effect in colorectal cancer ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The extent of cancer activity can be demonstrated by changes in cellular metabolic activity 21 . For example, the upregulation of glycolytic metabolism suggests exacerbation of COAD 22 , 23 while altered amino acid metabolism indicates metastasis, proliferation and drug resistance 24 26 . Normal bile acid metabolism contributes to the absorption of lipids, cholesterol and fat-soluble vitamins in the body and regulates the homeostasis of the epithelial environment of the gastrointestinal tract 27 .…”
Section: Discussionmentioning
confidence: 99%